(untitled) (Fiep Bulletin - online, 2014)
In the area of sports performance, the planning of preparation is something that is being developed since the 1910s, when the systematization of training began. Despite the immense advances in this area, there are other fields that still present great difficulties for not applying, or even not knowing these principles that are basic for sports training. In Music Performance, even to this day, the idea that in order to become a good musician, one must practice daily as much as possible is very common. This practice can be seen as imprudent and has been causing a significant number of musicians to present injuries, often disabling ones. This article aims to construct analogies between the sports training methodology and apply them to music performance. The theme requires a deeper investigation for the healthiest partnership between the areas. The merit of raising these questions relies, most of all, on the impact and changes in behaviour of the teachers that act in music performance instruction. In this context, it may contribute to the construction of new pedagogical practices that, besides being preventive in relation to the problems caused by training overload, may also maximize the effectiveness in the process of preparation, culminating with better results in concerts, recitals and auditions.